Axial and transverse permeability of unidirectional fiber-reinforced composites. Issue 4 (3rd April 2018) - Laghaei, Reyhaneh; Zarrebini, Mohammad; Soltani, Parham
Abstract: Unidirectional fibrous structures are of interest in composite materials processing for applications in which fluid is injected into preforms that have arrays of parallel fibers and their axes are oriented either perpendicular to or in line with the direction of resin flow. The stumbling block in the liquid molding of composites is the resin inﬁltration of the fibrous preform. Permeability of the fibrous preform determines the extent of resin infiltration. Despite conduction of considerable researches on various aspects of permeability, measurement and interpretation of this key property is still in its infancy. In this work, permeability of unidirectional fibrous performs in axial and transverse directions which, respectively, correspond to flow along and perpendicular to the axis of fibers were determined. This was achieved by generation of virtual randomly unidirectional fibrous structures using an in-house developed Matlab ® -based program. Permeability was computed by numerical solution of incompressible creeping Newtonian flow through the porous micro-structures. The results were compared with the published experimental and analytical models. The results were also compared with the experimental data and those of micro-computed tomography-based model of authors. Acceptable agreement between the results and previously published findings was observed. It was also established that randomly unidirectional structures exhibit high anisotropic behavior, possessing an approximate axial to transverse permeability ratio of 4:1.